Neutrinos From Individual Gamma-Ray Bursts in the BATSE Catalog - Guetta, D.; Hooper, D.; Alvarez-Muniz, J.; Halzen, F.; Reuveni, E. (arXiv, 2003)
We calculate the neutrino emission from individual gamma-ray bursts observed by the BATSE detector on the Compton Gamma-Ray Observatory. Neutrinos are produced by photoproduction of pions when protons interact with photons in the region where the kinetic energy of the relativistic fireball is dissipated allowing the acceleration of electrons and protons. We also consider models where neutrinos are predominantly produced on the radiation surrounding the newly formed black hole. From the observed redshift and photon flux of each individual burst, we compute the neutrino flux in a variety of models based on the assumption that equal kinetic energy is dissipated into electrons and protons. Where not measured, the redshift is estimated by other methods. Unlike previous calculations of the universal diffuse neutrino flux produced by all gamma-ray bursts, the individual fluxes (compiled at http://www.arcetri.astro.it/~dafne/grb/) can be directly compared with coincident observations by the AMANDA telescope at the South Pole. Because of its large statistics, our predictions are likely to be representative for future observations with larger neutrino telescopes. : 49 pages, 7 figures. Accepted for publication in Astroparticle Physics